Cytotoxic activity of methanolic fractions of different Marrubium spp. against melanoma cells is independent of antioxidant activity and total phenolic content - Malgorzata Kozyra; Agnieszka Korga; Marta Ostrowska; Ewelina Humeniuk; Grzegorz Adamczuk; Renata Gieroba; Anna Makuch‐Kocka; Jaroslaw Dudka (FEBS Open Bio)
The Marrubium genus (horehound) has proved to be an abundant source of biologically active compounds, but there is little knowledge about its potential anticancer activity. Moreover, some Marrubium species have not been the subject of study in this regard. In this study, we performed comparative analysis of phenolic acid (PhA) content and total phenolic content in fractions obtained from methanolic extracts of Marrubium vulgare L. (common horehound), Marrubium cylleneum Boiss. & Heldr. and Marrubium friwaldskyanum Boiss herbs. We examined the cytotoxicity of these fractions against a human melanoma cancer cell line (A375) and normal human skin fibroblasts (BJ) using a 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyl‐tetrazolium bromide test, cell cycle analysis and real‐time monitoring of cell viability. We detected caffeic, p‐coumaric, ferulic and gentisic acids among the PhAs. Although the extracts obtained demonstrated low total phenolic content and did not show significant antioxidative properties, the nonhydrolyzed PhA fraction exhibited cytotoxic activity against a human melanoma cancer cell line, without affecting normal fibroblasts. Both acidic and alkaline hydrolysis abolished this activity, indicating that the esterified forms of phenolic compounds caused the observed cytotoxic effects. Further investigation of these compounds may facilitate the development of novel drugs for cancer treatment.